53 The role of health networks in addressing violent injury. (20th November 2022) - Solhkhah, Ramon; Ranjan, Sheetal
Abstract : Context: Social determinants of health (SDH) are the 'conditions in which people are born, grown, live, work, and age' which impact a variety of health outcomes. The World Health Organization identifies SDH inequalities as a root cause of violent injuries. Emerging prevention and intervention programs have begun to leverage health networks (i.e., hospitals) to address SDH inequalities and prevent violent injury. Process: Hospital-based violence intervention programs (HVIPs) have formed to break cycles of community violence. These programs establish a continuum of care for violently injured people starting in the hospital and continuing after discharge. One HVIP is Project HEAL in New Jersey, United States. Analysis: The data used to inform this presentation are derived from a formative evaluation of JSUMC's Project HEAL. We will discuss: - The program's conceptualization, development, and implementation processes. - It's operations, and how they fit within the strategic vision of a large healthcare network. - Strategies for implementation and sustainability in the increasingly profit-driven model of healthcare systems. Outcomes: This presentation can assist healthcare networks interested in developing and sustaining innovative community-oriented programs using health-focused approaches to violence prevention and intervention. It will provide strategies on using the SDH framework to garner buy-in for such programs from administrators and health network leaders. Learning Outcomes: Attendees will learn how SDH inequalities increase the risk of violent injury and be introduced to innovative programs employing evidence-based solutions for violent injury prevention and intervention. Attendees will also learn strategies to make such programs sustainable and successful.